Science and religion in the classroom: A philosophical approach. Issue 1 (2nd January 2019) - Walker, Timothy
Abstract : This article is intended to contribute to the debate about the nature of a Catholic philosophy of education by exploring the philosophical issues involved in the apparent conflict between scientific and religious knowledge claims. The claim that modern science has rendered religious truth claims unreasonable appears to be influential among students of secondary school age. The suggestion is made here that the thought of Bernard Lonergan can usefully be deployed to help students in this age group to explore the nature of scientific and religious knowledge claims in greater depth. The contribution which Lonergan's philosophy can make to philosophy of education more generally is also indicated. Finally, the advantages of this approach for those involved in Catholic education are discussed.